2020
DOI: 10.7759/cureus.10795
|View full text |Cite
|
Sign up to set email alerts
|

Youtube as an Information Source During the Coronavirus Disease (COVID-19) Pandemic: Evaluation of the Turkish and English Content

Abstract: Introduction: YouTube is an important online source of information and has two billion users globally. Its viewing numbers tend to increase exponentially in extraordinary global situations. Our aim in this study was to review and evaluate the contents of the most frequently viewed YouTube videos during the Coronavirus disease 2019 (COVID-19) pandemic. Methods: In this qualitative study, contents of the most frequently viewed Turkish and English YouTube videos regarding the COVID-19 pandemic were exa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…High percentages of misinformation were also found when the search was conducted in English or on other platforms (e.g., Facebook and Twitter) ( Li et al., 2020 ; Ahmed et al., 2020 ; Ahmed et al., 2020 ). Similar findings were also reported by a considerable amount of studies ( Ahmed et al., 2020 ; Pulido et al., 2020 ; Moon and Lee, 2020 ; Bârgăoanu and Durach, 2020 ; Khatri et al., 2020 ; Ataç et al., 2020 ; D'Souza et al., 2020 ; Dutta et al., 2020 ; Kocyigit et al., 2020 ; Yüce et al., 2020 ; Yuksel and Cakmak, 2020 ; Kawchuk et al., 2020 ; Raja and Shaheed, 2020 ; Almomani and Al-Qur'an, 2020 ; Cuan-Baltazar et al., 2020 ; Szmuda et al., 2020 ; Moscadelli et al., 2020 ; Obiała et al., 2021 ; Mackey et al., 2020 ; Safarnejad et al., 2020 ; Tagliabue et al., 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…High percentages of misinformation were also found when the search was conducted in English or on other platforms (e.g., Facebook and Twitter) ( Li et al., 2020 ; Ahmed et al., 2020 ; Ahmed et al., 2020 ). Similar findings were also reported by a considerable amount of studies ( Ahmed et al., 2020 ; Pulido et al., 2020 ; Moon and Lee, 2020 ; Bârgăoanu and Durach, 2020 ; Khatri et al., 2020 ; Ataç et al., 2020 ; D'Souza et al., 2020 ; Dutta et al., 2020 ; Kocyigit et al., 2020 ; Yüce et al., 2020 ; Yuksel and Cakmak, 2020 ; Kawchuk et al., 2020 ; Raja and Shaheed, 2020 ; Almomani and Al-Qur'an, 2020 ; Cuan-Baltazar et al., 2020 ; Szmuda et al., 2020 ; Moscadelli et al., 2020 ; Obiała et al., 2021 ; Mackey et al., 2020 ; Safarnejad et al., 2020 ; Tagliabue et al., 2020 ).…”
Section: Resultssupporting
confidence: 88%
“…They analyzed the quality of YouTube videos in six languages: Arabic, Bengali, Dutch, English, Hindi, and Nigerian, finding a MICI score of 5.68 [14]. In another study, Atac et al examined the quality of YouTube videos about COVID-19 and found a MICI score of 2.76 for English language videos and 3.33 for Turkish language videos [15]. A wide range of MICI scores are reported in the literature, perhaps because of the constant flow of new information about COVID-19, the different languages of the videos reviewed, and the different target audiences of the videos.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, studies on the transmission of text information have used a variety of different platforms as data sources, including Twitter [ 24 , 25 ], Weibo [ 26 ], and Facebook [ 27 ]. However, most research on epidemic information spread in the form of video has used the YouTube platform as the information source [ 28 , 29 , 30 , 31 ]. Compared with research on traditional text, research on videos tends to focus on a relatively single platform; there are many other emerging video platforms worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, previous studies on the factors affecting the popularity of COVID-19 videos have mainly been conducted from the perspective of certain video features [ 28 , 30 ], while few studies have comprehensively considered various indicators of video features. In addition, few studies have considered the effects of uploader features on video popularity.…”
Section: Introductionmentioning
confidence: 99%